Structural controls on rupture extent of recent Sumatran Fault Zone earthquakes, Indonesia - Salman, Rino (2020)
We present geodetically derived coseismic slip models for four Mw ~6 strike-slip earthquakes that struck the mainland island of Sumatra, Indonesia, between 2007 and 2016. Three of these earthquakes ruptured segments of the Sumatran Fault Zone: the 2007 Mw 6.3 and 6.4 Lake Singkarak doublet, and the 2009 Mw 6.6 Dikit event. The fourth earthquake, the 2016 Mw 6.6 Pidie Jaya event, ruptured an unmapped active fault in a region of historically low seismicity near the northern coast of Aceh. Our results suggest that (1) the estimated rupture extents of the 2007 Lake Singkarak doublet and 2009 Dikit event were limited by geological structures such as step overs that define segment boundaries, (2) the 2016 Pidie Jaya event did not produce surface rupture despite the fact that it produced large shallow slip of more than 2.5 m, and (3) the remaining seismic gaps on the Sumatran Fault Zone are primarily located between the equator and northern Sumatra. We strongly recommend that seismic hazard assessment for densely populated areas in Sumatra include threats not only from the Sumatran Fault Zone but also from additional potentially active faults outside of the main Sumatran Fault Zone.